ANALISIS STABILITAS LERENG DI KAKI GUNUNG SUMBING - Arrizka Yanuar A; Dwi Sat Agus Yuwana; Muhammad Amin (Universitas Tidar, 2017)
Balesari village of Windusari sub-district of Magelang regency located at the foot of the mountain SUMBING with a height of 350 to 1050 meters above sea level. This research was conducted by analyse the stability of steep slopes through soil physical properties using Bishop Morgenstern method. The analytical approach used is deterministic two-dimensional. Primary data obtained from measurements of the slope directly by using Theodolite and took soil samples at each location. The soil samples were tested at the Laboratory of Soil Mechanics to get the parameters of soil physical properties such as grain gradation, void ratio ( ), the soil volume weight ( ), the friction angle ( ), the value of cohesion (c). The result of study states the value of soil cohesion in the hamlet Mojo categorized loam, while in the hamlet of Malanggaten categorized clay loam. The results of soil physical properties shows the value of the Factor of safety (F) at the measurement point in the hamlet of Mojo and Malanggaten are 0.89, 0.31 and 0.41 respectively. Thus the stability of the slope in the village is not safe.